Workshop Strategi dan Implementasi Pengelolaan Laboratorium IPA yang Efektif: Program Pengabdian Kepada Masyarakat Bagi Guru IPA/Fisika dan Tenaga Laboratorium Kabupaten Gowa - Ikbal, Muh. Syihab; Suhardiman; Ali, Mukti; Sulman (KHIDMAH: Jurnal Pengabdian Masyarakat, 2025)
The workshop "Strategy and Implementation of Effective Science Laboratory Management" is a community service initiative based on service learning, aimed at improving the capacity of science/physics teachers and laboratory personnel in Gowa Regency in managing laboratories. The primary focus of this activity is to provide a comprehensive understanding of the management of laboratory equipment, materials, and environments to support a high-quality learning process and minimize the risk of accidents. The service method used follows the service learning approach, which consists of three main stages: preparation, implementation, and evaluation. The results of this activity indicate that participants' responses to both the technical aspects and content of the workshop were at a very positive level. Their response to the relevance of the material was highly favorable, and there was a significant improvement in their understanding of science laboratory management after participating in the workshop. Thus, the knowledge and experience gained by the participants are expected to be effectively implemented in school laboratories.